2004
DOI: 10.1108/09513540410512181
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the training program for Greek Olympic education

Abstract: The aim of this study was to develop an instrument to evaluate the educational program's training. The program used for this purpose was the Olympic Education Program, which has been implemented in Greek primary and secondary schools since 2000. First, the face validity of items was evaluated, second, the pool of the items selected was factor analyzed. Exploratory factor analysis indicated a three-factor solution with high internal consistency. The instrument, Professional Development Evaluation Form of the Ol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 12 publications
0
10
0
2
Order By: Relevance
“…The three factors obtained were training, study groups, and total impression. Results indicated that the instrument had adequate psychometric properties (Grammatikopoulos, Papacharisis, et al, 2004).…”
Section: Methodsmentioning
confidence: 97%
See 2 more Smart Citations
“…The three factors obtained were training, study groups, and total impression. Results indicated that the instrument had adequate psychometric properties (Grammatikopoulos, Papacharisis, et al, 2004).…”
Section: Methodsmentioning
confidence: 97%
“…First, the Professional Development Evaluation Form (PDEF) instrument was developed to evaluate the training program itself (Gramrnatikopoulos, Papacharisis, Koustelios, Tsigilis, & Theodorakis, 2004). The PDEF instrument consisted of three factors containing 2 l items.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Para o desenvolvimento da avaliação de programas de treinamento são utilizadas inú-meras ferramentas (Campbell, 1998;Kuprenas, Madjidi e Alexander, 1999;McMillan, Bunning e Pring, 2000;Tennant, Boonkrong e Roberts, 2002;Wong e Wong, 2003;Featherstone et al, 2004;Grammatikopoulos et al, 2004;Litarowsky, Murphy e Canham, 2004;Lingham, Richley e Rezania, 2006;Westbrook et al, 2008). No entanto, essas ferramentas, em sua grande maioria, apresentam limitações e lacunas que podem comprometer o processo de avaliação (Tasca, Ensslin e Ensslin, 2009).…”
Section: Introductionunclassified
“…Still, the model is seen as offering flexibility to users as it permits them to align outcomes of training with other organizational tools (e.g., company reports and greater commitment of employees) (Abernathy, 1999). Though the model has been used for 3 decades in the evaIuation of commercial training programs, some scholars have suggested its use for research studies of academic programs and have used it for the purpose (Tarouco & Hack, 2000;Boyle & Crosby, 1997), while others have suggested a combination of the model with other professional development tools (Grammatikopoulos, Papacharisis, Koustelios, Tsigilis, & Theodorakis, 2004). In particular, level four of Kirkpatrick"s model is highly relevant to distance learning as it seeks tangible evidence that learning has occurred, as does level two (Galloway, 2005).…”
Section: )mentioning
confidence: 99%